(untitled) (Seminar_BG, 2025)
The context in which internet memes develop, the development of web 2.0 and the ambitions for web 3.0 are inextricably linked to active participation and interactivity. Anyone with access to a computer and the internet can access free scientific articles, images, music, videos, etc. and create their own (audio)visual creations. The text examines the influence of internet memes on communication and language. The research questions are how communication (on – in the digital space and off-line – live) and linguistics have changed as a result of the influence of internet memes? Can we talk about an (internet) memetic language and what are the differences between memetic language and traditional language rules? How can memetic language systems be translated using concepts from linguistics? What are the results of the influence of internet memes on communication and language? An attempt will be made to answer these questions by examining examples of the influence of internet memes on various areas: 1. Literacy in digital communication. 2. Visual images in the fields of art, graphic and web design, and audio-visual works. 3. Human behavior. References Álvarez, David. 2024. Nostalgia Isn’t What it Used to Be: On Vaporwave’s Glitched, Aspirational Aesthetics. Iluminace. 36. 107-126. 10.58193/ilu.1788. Baudrillard, J. 1988. Selected Writings, ed. Mark Poster. Stanford, Calif: Stanford Univ. Press Davison, Patrick. 2012. The Language of Internet Memes. 10.18574/nyu/9780814763025.003.0013. Decheva, T. 2025. "Glich-art i fotografskiyat obraz. Deformatsii i schupvane na tsifrovite obrazi". Spisanie Kino. https://spisaniekino.com/%D0%B3%D0%BB%D0%B8%D1%87-%D0%B0%D1%80%D1%82-%D0%B8-%D1%84%D0%BE%D1%82%D0%BE%D0%B3%D1%80%D0%B0%D1%84%D1%81%D0%BA%D0%B8%D1%8F%D1%82-%D0%BE%D0%B1%D1%80%D0%B0%D0%B7-%D0%B4%D0%B5%D1%84%D0%BE%D1%80%D0%BC%D0%B0%D1%86%D0%B8%D0%B8-%D0%B8-%D1%81%D1%87%D1%83%D0%BF%D0%B2%D0%B0%D0%BD%D0%B5-%D0%BD%D0%B0-%D1%86%D0%B8%D1%84%D1%80%D0%BE%D0%B2%D0%B8%D1%82%D0%B5-%D0%BE%D0%B1%D1%80%D0%B0%D0%B7%D0%B8.html (last seen 27. 02. 2025) Douglas, Nick. (2014). "It’s Supposed to Look Like Shit: The Internet Ugly Aesthetic". Journal of Visual Culture. 13. 314-339. 10.1177/1470412914544516. Dovydaitis, Gytis. 2021. "Celebration of the Hyperreal Nostalgia: Categorization and Analysis of Visual Vaporwave Artefacts". Art History & Criticism. 17. 113-134. 10.2478/mik-2021-0010. gamedev, 2022. What is the difference between a bug and a glitch? Is it just the same thing or is there a difference?, Reddit. https://www.reddit.com/r/gamedev/comments/qe4eqi/what_is_the_difference_between_a_bug_and_a_glitch/ (last seen 25. 02. 2025) Genova, D. 2020. "Internet memeta i komunikatsia onlayn". Balgarski folklor, 3/2020. Glitsos, Laura. 2018. "Vaporwave, or music optimised for abandoned malls". Popular Music. 37. 100-118. 10.1017/S0261143017000599. Grundlingh, Lezandra. 2017. "Memes as speech acts". Social Semiotics. 28. 10.1080/10350330.2017.1303020. Ivanova, Maria. 2022. "Memetata v novinite i memetata kato novini". Medialog, 11/2022, 153-184. Jenkins, H., et al. 2006. Confronting the Challenges of Participatory Culture: Media Education for the 21st Century. An Occasional Paper on Digital Media and Learning. Kostadinovska-Stojchevska, Bisera & Shalevska, Elena. 2018. "INTERNET MEMES AND THEIR SOCIO LINGUISTIC FEATURES". English Language and Linguistics. 2. 10.5281/zenodo.1460989. Krustovski, J. 2023. What Is Plunderphonics. https://microgenremusic.com/category/genres/plunderphonics/ (last seen 27.02.2025 г.) Kuipers, G. 2002. "Media culture and internet disaster jokes: Bin Laden and the attacks on the World Trade Center". European Journal of Cultural Studies, 5(4). doi: 10.1177/1364942002005004296 Krustovski, J. 2023. What Is Plunderphonics. https://microgenremusic.com/category/genres/plunderphonics/ (last seen 27.02.2025 г.) Lessig, Lawrence. 2008. Remix: Making Art and Commerce Thrive in a Hybrid Economy. 10.5040/9781849662505. Loignon, Guillaume & Messier, Philippe. 2020. Vaporwave pedagogy: Multimodal learning with an internet music microgenre. 16. McLeod, Ken. 2018. "Vaporwave: Politics, Protest, and Identity". Journal of Popular Music Studies. 30. 123 142. 10.1525/jpms.2018.300409. Mick-Evans, K. 2019. One Does Not Simply Preserve Internet Memes: Preserving Internet Memes Via Participatory Community -Based Approaches. 10.13140/RG.2.2.18093.54240. Milner, R., 2016. The world made meme: Discourse and identity in participatory media. (Unpublished doctoral dissertation). University of Kansas, Lawrence, KS. Retrieved from academia.edu Milner, R. M. 2012. “The World Made Meme: Discourse and Identity in Participatory Media.” PhD diss., University of Kansas. Accessed March 13 2015. https://kuscholarworks.ku.edu/bitstream/handle/ 1808/10256/Milner_ku_0099D_12255_DATA_1.pdf?sequence=1. Miltner, K. M. 2014. “’There’s no place for lulz on LOLCats’: The role of genre, gender, and group identity in the interpretation and enjoyment of an Internet meme". First Monday, 19(8). https://doi.org/10.5210/fm.v19i8.5391 Miltner, K.M. and Highfield, T. 2017. "’Never Gonna GIF You Up’: Analyzing the Cultural Significance of the Animated GIF". Social Media and Society. Mineva, Mila. 2022. "’Da ne izliza’ ili populyarnata kultura kato pole za eksperimentalni praktiki", Seminar_BG, 21. https://www.seminar-bg.eu/spisanie-seminar-bg/broy21/798-da-ne-izliza.html Orlovas, Vygintas. 2019. “The Influence of Internet Culture on the Shifts in Aesthetics. A Practice-Based Approach to Vaporwave.” Sovijus 7, no. 1 (2019): 129–137. Perov, T. 2023. "Edno neobiknoveno zhivotno: Kotarakat Rumen ima 60 hil. posledovateli vav Facebook". BulgariaOnAir. https://www.bgonair.bg/a/36-sutreshen-blok/302044-edno-neobiknoveno-zhivotno-kotarakat-rumen-ima-60-hil-posledovateli-vav-facebook (last seen 13. 02. 2025 g.) Pinto, J. 2017. Cultural Ideas Essay. Vaporwave & Postmodernism: An Analytical Interpretation of Blank Banshee. SAE Institute London. Semotiuk, O., & Shevchenko, V. 2023. "Making fun of power: political cartoons and memes about President Zelensky. Quantitative and qualitative analysis". The European Journal of Humour Research, 10(4), 82–98. https://doi.org/10.7592/EJHR.2022.10.4.703 Shifman, L. 2014. “The Cultural Logic of Photo-Based Meme Genres.” Journal of Visual Culture 13 (3): 340–358. doi:10.1177/1470412914546577. Soriano, Ezequiel. 2022."Internet vernacular creativity. Vaporwave, counterculture and copyright". ISEA2022 Proceedings: 556-561 Tay, G. J. S. 2014. "Binders full of LOLitics: Political humour, inter net memes, and play in the 2012 US Presidential Election (and beyond)". European Journal of Humour Research 2(4): 46– 73 Terziev, K. 2012. Rekompozitsia- avtor, media i proizvedenie v epohata na digitalnoto proizvodstvo. Sofia: Iztok-zapad. [in Bulgarian] Vadde, Aarthi. 2017. "Amateur Creativity: Contemporary Literature and the Digital Publishing Scene". New Literary History. 48. 27-51. 10.1353/nlh.2017.0001. Wiggins, B. 2019. The Discursive Power of Memes in Digital Culture. Routlege Studies in New Media and Cyberculture. 52 Vanderbilt Avenue, New York, NY 10017. Zavala Barreda, Karla. 2018. Dystopian Shopping Malls: Vaporwave and The Ghosts of The Future. Paper presented at Cool Retro Camp Trash, Aesthetic Concepts in Popular Culture, Freiburg, Freiburg University.